MATCHMAKING RELATIONS IN UZBEKISTAN - Karimova Medina Botirzhonovna; Umarova Zilolakhan (American Journals Publishing, 2024)
The invention of the article uzbeklarning the marriage of Bulgan sovhilik Bilan berklik urf-the custom of Andijan region wintkazilgan ethnographic researcher based on yeritib berilgan.
Keywords: Uzbekistan, sovchilik, Andijan region, kizlar, Islam religion.